Suppression of Esophageal Cancer Stem-like Cells by SNX-2112 Is Enhanced by STAT3 Silencing - Xu, Dan-dan; Chen, Su-hong; Zhou, Peng-jun; Wang, Ying; Zhao, Zhen-dong; Wang, Xia; Huang, Hui-qing; Xue, Xue; Liu, Qiu-ying; Wang, Yi-fei; Zhang, Rong (Frontiers in Pharmacology, 2020)
Many studies demonstrate that cancer stem cells (CSCs) or tumor-initiating cells (TICs) are responsible for the proliferation, chemotherapy resistance, metastasis, and relapse. We and others have previously shown that the STAT3 signaling pathway is required for CSCs and TICs growth. Recent reports indicated that the Hsp90 is also essential for survival for the CSCs or TICs. However, the effect of Hsp90 inhibitor SNX-2112 with knockdown of STAT3 (shSTAT3) on the proliferation of the esophageal cancer stem-like cells (ECSLCs) remains unclear. Here we explored the association between SNX-2112 with shSTAT3 to suppress ECSLC growth. We found that the expression level of both STAT3 and p-STAT3 was higher in clinical esophageal cancer tissue compared with the adjacent normal tissue according to western blot and qPCR analysis. Furthermore, KEGG enrichment analysis demonstrates that STAT3 was overpexpressed in clinical specimen. We demonstrated that SNX-2112, a Hsp90 inhibitor, inhibited the proliferation, decreased the ABCB1 and ABCG2 gene levels, reduced the colony formation capacity of the ECSLCs, which is enhanced by STAT3 silencing. Flow cytometry analysis revealed that the combination of SNX-2112 with STAT3 knockdown significantly induced apoptosis and cell cycle arrest at G 2 /M in ECSLCs. The proliferation pathway proteins including P38, JNK, Erk were reduced. Furthermore, the effect of both interventions was also seen on the phosphorylation of client proteins of Hsp90. In addition, SNX-2112 with shSTAT3 inhibited the proliferation of ECSLCs in vivo. Furthermore, STAT3 overexpression abolished the effects of SNX-2112 with shSTAT3 on the proliferation inhibition of ECSLCs. Hence, these results provide a rationale for the therapeutic potential of the combination of SNX-2112 with shSTAT3 for esophageal cancer and and may suggest new targets for clinical intervention in human cancer.